REBORN OF ROMANIAN BRANDS BY E-COMMERCE - Voicilaş, Dan-Marius (Economics of Agriculture, 2012)
The paper analyses the evolution of the Romanian traditional brands during the last 20 years. We started the analysis with the presentation of the most famous Romanian brands during the communist period. Then, we presented the transition of the traditional brands to the market economy, under the influence of structural transformations in economy, globalization and strong competition on the market. Some firms chose special strategies to enter on market or extend their share on market. Among them, the "reactivation" of old brands, from communist period, has an important place. The method seems to be successful and is based on the psychological implications generated by certain products in the nostalgic consumers minds. The analysis is close correlated with the evolution of the Internet and E-commerce. The new techniques of commercialization of the goods comprise the Internet use and promotion by Internet. That is why we will also present the impact of the Romanian traditional brands on Internet and E-commerce. We intend to know if is possible for old brands to compete on the market, if there is enough capacity for the entrepreneurs to stand out on the market, to protect and promote their products in the tough competition environment, subject to globalization, regardless of the fact that they take over an already consecrated mark or create a new one.